Intersectoriality in violence care against chronic illnes children (Research, Society and Development, 2020)
This article starts from the experience of situations of violence against children in a pediatric institution of a medium and high complexity of the SUS that serves chronically ill children and adolescents. It aims to analyze an intersectoral approach as one of the strategies in the children care of with this profile of illness and who experience situations of intrafamily violence. This is an exploratory and descriptive study, using analysis in medical records and data collection in compulsory notification forms from the Information System and Notifiable Diseases (SINAN). The period of the research was from September 2017 to September 2018. The results known the occurrence of important referrals to the social assistance network, however the access of these families was sometimes hampered, and the returns received by the referred institutions were few.